Compreensão leitora em língua estrangeira: uma perspectiva saussuriana para o ensino em escolas de idiomas - Meurer, Daiane (My University, 2019)
This dissertation aims at proposing reading comprehension learning situations in English, based on Saussurian concepts of value, system, and the notion of relation, for students at level B1, of the Common European Framework of Reference (CEFR), in schools of languages. To this end, in addition to the study of the theoretical assumptions that underlie this study, the criteria proposed by the QECR regarding reading comprehension skills for teaching and learning a foreign language are examined. It also explains the global language status acquired by the English language at world level, as well as the influence of cultural aspects in the learning of a foreign language, and the relationship between language and culture through the anthropological bias. It has as object of study activities of a collection of didactic books (workbook and student book), used in a language school. From this, possibilities of reading teaching in English, that collaborate to the development of abilities of reading comprehension, are suggested, aiming at the constitution of the sense of discourse. This study seeks to broaden the research on the process of teaching foreign languages as it proposes new perspectives for the approach of reading in language schools and expands studies on the issue of teaching in postgraduate school.
Esta dissertação visa a propor situações de aprendizagem de compreensão leitora, em língua inglesa, fundamentadas nos conceitos saussurianos de valor, sistema, e na noção de relação, para alunos em nível B1, do Quadro Europeu Comum de Referência (QECR), em escolas de idiomas. Para isso, além do estudo dos pressupostos teóricos que embasam esta pesquisa, são examinados os critérios propostos pelo QECR, no que tange à habilidade de compreensão leitora, para o ensino e a aprendizagem de língua estrangeira. Explana-se ainda o status de língua global, adquirido pela língua inglesa, em nível mundial, bem como a influência de aspectos culturais na aprendizagem de uma língua estrangeira, e a relação entre língua e cultura pelo viés antropológico. Tem-se como objeto de estudo atividades de uma coleção de livros didáticos (workbook e student book), utilizados em uma escola de idiomas. A partir disso, sugerem-se possibilidades de ensino de leitura em língua inglesa, que colaborem para o desenvolvimento de habilidades de compreensão leitora, objetivando a constituição do sentido do discurso. Este trabalho busca contribuir para as pesquisas acerca do processo de ensino de línguas estrangeiras, na medida em que propõe novas perspectivas para a abordagem da leitura, em escolas de idiomas, e amplia os estudos sobre a questão do ensino na pós-graduação.
Keywords: Língua inglesa - Estudo e ensino; Escolas de línguas; Compreensão na leitura; English language - Study and teaching; Language schools; Reading comprehension